Comparison of Diagnostic Accuracy of Cone Beam Computed Tomography and Digital Radiography for Detection of Vertical Root Fractures with and without Gutta Percha - Valizadeh, Solmaz; Azimi, Fatemeh; Babazadeh, Hosein; Azizi, Zeynab (Journal of Dental School, 2019)
Objective: Diagnosis of vertical root fractures (VRFs) is critical in endodontics; which most of the times occurs in endodontically treated teeth with root canal fillings such as gutta percha. Despite Cone Beam Computed Tomography (CBCT) has significantly enhanced image quality compared to digital radiography (DR) which aid the diagnosis, artifacts has remained as a problem in VRF detection. The aim of this study was to compare accuracy of CBCT and digital radiography system in vertical root fracture with presence and absence of gutta-percha. Methods: In this experimental in vitro study, 60 premolar teeth were cut at the cementoenamel junction .The teeth were randomly divided into two groups; for one group root canal therapy was done and the roots filled with gutta-percha. The other group was the control one .At the first stage CBCT scan and digital radiography was done and subsequently, vertical root fractures were induced for all samples. Then all the teeth were scanned by CBCT and digital radiography system and three observer assessed CBCT images and digital radiographies for presence of vertical root fracture. ANOVA and weighted Kappa tests estimated the diagnostic accuracy values and inter-observer agreement. Results: All values for CBCT were higher than Digital radiography except for absolute specificity and negative predictive value (p=0.409, p=0.053). In both imaging systems, there was no statistical difference between presence and absence of gutta-percha. (p=0.599, p=1.000, p=0.673, p=0.373). Conclusion: Diagnostic accuracy of vertical root fracture was not influenced by presence or absence of gutta-percha. Additionally, CBCT imaging system had higher diagnostic accuracy in comparison of digital radiography.